ОТ ДРУЖИННОЙ ЛЕТОПИСИ - К ВОИНСКОЙ ПОВЕСТИ: ОТРАЖЕНИЕ НАЧАЛЬНЫХ ЭТАПОВ РАЗВИТИЯ ВОЕННОГО ДЕЛА В ДРЕВНЕРУССКОЙ ЛИТЕРАТУРЕ XI-XVI ВЕКОВ (Библиосфера)
The article analyzes historical and cultural factors of the origin of military chronicles in ancient Russia and the formation a genre variety in ancient Russian literature - war stories.